Práticas informacionais e tratamento de dados pessoais: análise do fluxo informacional nas rotinas contábeis - Pessoa, Luiz Gustavo de Sena Brandão (2023)
In the information society, the treatment and use of data is a topic that has been widely debated by academic and professional environments. However, freedom in the use and sharing of data without the minimum criteria has generated discussions on the issue of privacy and protection of personal data. With the advent of the General Law for the Protection of Personal Data (LGPD), public and private sectors of society now have criterion for the treatment, use and sharing of personal data. This thesis aims to analyze the information flow in personal data available in accounting offices in order to establish guidelines to enable the control of its circulation. The research is exploratory and descriptive, an in loco field research was carried out in 17 counties, covering all regions of the State of Paraíba - Brazil. The empirical field consisted of 88 accounting professionals who own or are responsible for offices, for the development of their activities. It starts from the premise that the informational flows that transit in the environments of these professionals, through the collection, storage, recovery and disposal, do not have data management, which compromises the legitimate and specific purposes of use, putting at risk the continuity of their business due to LGPD sanctions. The results showed vulnerabilities in the information flow process that can be minimized or corrected with the proposed guidelines. It is expected that this research will contribute to the improvement in the management of the life cycle of personal data in the environments of accounting professionals.